The Influence of Leadship Style, Discipline and Evironment on Employee Performance at PT Giri Palma Moderated by Motivation - Sejati, Samporno; Riyanto, Setyo (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2025)
This study investigates the influence of leadership style, work discipline, and work environment on employee performance, with work motivation examined as a moderating variable, in the context of PT Karya Giri Palma, one of the prominent furniture companies in Malang, Indonesia.. The study employed a quantitative approach and involved 110 employees, selected from a total population of 150 using a simple random sampling technique based on the Slovin formula. The analysis was conducted using Partial Least Squares (PLS) with the SmartPLS 4.0 software. The results show that work discipline significantly influences employee performance, whereas leadership style and work environment do not have a statistically significant effect. Additionally, work motivation does not moderate the relationships between the independent variables and employee performance. These findings underscore the critical importance of work discipline in enhancing employee outcomes and offer practical insights for improving human resource strategies in similar manufacturing contexts. The study also contributes to the literature by clarifying the limited moderating role of motivation in performance-related models.